Collaborative Governance dalam Pengawasan Pemilihan: Studi Hubungan Antar-Lembaga Bawaslu Kabupaten Badung Tahun 2024 - I Putu Hery Indrawan; Ida Ayu Putu Sri Widnyani (Student Research Journal, 2026)
This study aims to analyze the forms, patterns, and challenges of collaborative governance in the supervision of the 2024 Badung Regent and Vice Regent Election. The main issue examined is the inter-institutional relationship established by the Badung Regency Election Supervisory Agency (Bawaslu) in strengthening electoral supervision through cooperation with various stakeholders. This research employs a descriptive qualitative approach using document analysis. The primary data were derived from the Final Report on Prevention, Supervision, Participatory Supervision, and Inter-Institutional Relations of Bawaslu Badung Regency in 2024, while supporting data were obtained from the Final Report on the Handling of Violations in the 2024 Badung Regent and Vice Regent Election. The unit of analysis consists of official documents containing data on memoranda of understanding, audiences, coordination meetings, participatory supervision, and the dynamics of alleged electoral violations. The findings indicate that collaborative governance is reflected in five main dimensions: starting conditions, institutional design, facilitative leadership, collaborative process, and outcomes. Bawaslu Badung Regency’s collaboration was manifested through 16 memoranda of understanding, 9 audiences, cross-actor coordination forums, and the involvement of media, universities, civil society organizations, religious organizations, and local communities. However, this collaboration still faces challenges, including the need for technical follow-up, stronger routine communication, and systematic evaluation of cooperation. This study contributes to public administration scholarship by positioning electoral supervision as a collaborative governance practice rather than merely a technical institutional function.